2008
DOI: 10.1002/bdd.624
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of gender in the oral pharmacokinetics of clindamycin in humans

Abstract: Clindamycin is an antimicrobial agent metabolized by CYP3A4. Gender may influence the pharmacokinetics of drugs metabolized by this pathway, however, no information about differences in the pharmacokinetics of clindamycin in men and women is available. The purpose of this study was to evaluate gender differences in clindamycin oral pharmacokinetics. Twenty-four subjects (11 men and 13 women) received an oral 600 mg dose of clindamycin under fasting conditions and plasma concentrations were obtained at selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 13 publications
2
10
0
Order By: Relevance
“…[23][24][25] Although several studies report higher CYP3A activity in women, 26-28 others found no sex effect. 29 Our results indicate that sex plays an important role on CYP3A activity and quinine disposition. In contrast to our findings, Mirghani et al did not find a sex effect on quinine metabolic ratio in Tanzanians.…”
Section: Discussionmentioning
confidence: 63%
“…[23][24][25] Although several studies report higher CYP3A activity in women, 26-28 others found no sex effect. 29 Our results indicate that sex plays an important role on CYP3A activity and quinine disposition. In contrast to our findings, Mirghani et al did not find a sex effect on quinine metabolic ratio in Tanzanians.…”
Section: Discussionmentioning
confidence: 63%
“…For example, women exhibited higher plasma concentrations of the antibacterial drug clindamycin than men in one study after an oral 600 mg dose, but these concentrations were similar when normalized for body weight (del Carmen Carrasco-Portugal et al 2008). A similar study demonstrated that after a single oral 200 mg dose of fluconazole, a commonly used antifungal drug, in healthy Chinese adults, sex-related differences in AUC, C max , and volume of distribution which directly correlated with body weight were observed .…”
Section: Distributionmentioning
confidence: 92%
“…It has been described that activity of this isozyme is 20 to 50% higher in women when compared with men [45]. However, other authors have not found any difference between genders when oral pharmacokinetics of drugs has been compared [47,53,54]. Additionally to these studies, it has been evaluated the differences in the urinary excretion of 6-betahydroxycortisol/cortisol (a marker of hepatic CYP3A4) in Asian and Caucasian women [55].…”
Section: Metabolismmentioning
confidence: 99%